An Occult Royal Wedding: Public State Ceremonies as Rituals of Civil Irreligion. (8th December 2018) - Toseland, Nicholas
Abstract : This article explores the contested nature of the meaning of state ceremonies, focussing on alternative accounts of the United Kingdom's 2011 Royal Wedding between William Windsor and Kate Middleton. Although state ceremonies are ostensibly secular affairs, utilizing religious symbolism for purely ceremonial reasons, there are those who think differently. David Icke perceives a hidden, satanic symbolism and deploys various interpretive strategies including the numerology of time, symbology of ceremonial objects, and genealogy of participants. Building on Bellah's concept of "civil religion, " this article looks at competing expressivist and instrumentalist analyses alongside the interpretive strategies of Icke, and other 'truth-seeker' bloggers, for whom the Royal Wedding, alongside other state rituals, functions as a nefarious ritual of civil irreligion.